Linguopragmatic means of expressing subjective modality in commercial and political advertising slogans - Sherkulova , Makhliyo (The Lingua Spectrum, 2025)
This research explores the linguopragmatic means used in commercial and political advertising slogans to effectively express attitudes. The aim of the study is to analyze the role of linguistic strategies such as hedging, politeness markers, and rhetorical devices in conveying specific attitudes towards products or political messages. Methodologically, the research employs a qualitative analysis of a corpus of advertising slogans from both commercial and political contexts. It aims to identify the patterns and strategies advertisers and politicians use to shape attitudes and perceptions among their target audiences through language. The study highlights the significance of linguopragmatic tools in shaping views within advertising and political discourse. It emphasizes how linguistic choices influence message reception, consumer behavior, and public opinion. Understanding these linguistic strategies provides valuable insights for marketers, advertisers, and political activists, enabling them to communicate their messages effectively and influence audience attitudes. By exploring the pragmatic aspects of language in advertising discourse, the research contributes to the fields of discourse analysis and applied linguistics, offering both theoretical and practical foundations for analyzing persuasive communication.